Efforts to increase English vocabulary skills using puppet theater and flashcards at TK Islam Amaryllis, Cibubur - Sheila Wijayanti; Syahadah Albaqiyatul Karimah (Community Empowerment, 2023)
This community service activity aims to increase English vocabulary in daily life for the kindergarten level at TK Islam Amaryllis, Cibubur. At the kindergarten stage, aspects of physical and psychosocial development are needed, which include intellectual, language, motoric, and social-emotional development. Besides that, especially the introduction of English vocabularies. Socialization, demonstration, and practice (with puppet theater and flashcards as media), and evaluation are the stages carried out in this program. The result is that students at TK Islam Amaryllis, Cibubur, have increased their knowledge of English vocabulary, which can be used for further levels of education by using or demonstrating learning media, namely puppet theater and flashcards.